Peran Knowledge Management Dalam Manajemen Sumber Daya Manusia Internasional - Apsoh Nurjanah; Maria Dwi Puspasari (Shofanah Media Berkah, 2026)
International Human Resource Management (IHRM) has emerged as a critical instrument for multinational enterprises in coordinating a geographically dispersed global workforce. Amidst the complexities of cultural differences, linguistic barriers, and diverse local regulations, enterprises are required to formulate adaptive strategies to align global employee performance with collective organizational goals. One strategic framework of growing importance in international HRM is the integration of Knowledge Management. This approach facilitates enterprises in identifying, documenting, distributing, and optimally utilizing intellectual assets across global business units. This article analyzes the contemporary challenges of international HRM, the strategic contribution of Knowledge Management in supporting global HR operations, and the systemic integration model between the two. The analysis indicates that this integration yields massive positive outcomes, ranging from productivity acceleration and strategic decision-making efficiency to enhanced employee loyalty and engagement. Through this holistic approach, global corporations can construct an inclusive, collaborative, and innovative work ecosystem amidst intense competition in the global market.